Cardiology's 10 Greatest Discoveries of the 20th Century - Mehta, Nirav J. (2002)
We present a brief summary of the 10 greatest cardiologic developments and discoveries of the 20th century. Described are electrocardiography; preventive cardiology and the Framingham Study; “lipid hypotheses” and atherosclerosis; coronary care units; echocardiography; thrombolytic therapy; cardiac catheterization and coronary angiography; open-heart surgery; automatic implantable cardiac defibrillators; and coronary angioplasty. These topics are the personal choices of the authors. (Tex Heart Inst J 2002;29:164–71)